The Influence of Debt to Assets Ratio and Long Term Debt to Equity Ratio on Return On Investment (Case Study at PT. Indosat Tbk for the Period 2014-2023) - Muhammad Adi Tegar; Neneng Yanti Andriani (Escalate : Economics and Business Journal, 2024)
This study was conducted to determine the influence of debt to asset and long term debt to equity ratio on Return on Investment at PT. Indosat, Tbk for the period 2014-2023. The research method used was descriptive associative method. The population in this study was secondary data from the financial reports of PT. Indosat, Tbk. The sample taken used nonprobability sampling technique with purposive sampling method with specific criteria, namely the financial reports per quarter of PT. Indosat, Tbk for the years 2014-2023. To test the influence analysis, Pearson product moment correlation analysis, coefficient of determination analysis, hypothesis testing using t-test and F-test, and multiple linear regression analysis were used. Based on the analysis conducted, it was shown that the correlation value of debt to asset to return on investment is 0.557 which falls into the moderate category, and the correlation value of long term debt to equity ratio to return on investment is 0.012 which falls into the very low category. Based on the determination analysis conducted, it was shown that the contribution of the independent variables (debt to asset and long term debt to equity ratio) to the dependent variable (return on investment) is 0.035 or 3.5%. In conclusion, 3.5% while the remaining 96.5% (100% - 3.5%) is influenced by other variables outside the study.